Average time of dispersal and germination of Fabaceae seeds retrieved from goat feces - Tatiana Oliveira da Silva; Henrique Duarte Vieira; Bruno Borges Deminicis; Norberto Silva Rocha; Renata Vianna Lima; Leonardo Siqueira Glória (Semina: Ciências Agrárias, 2019)
This study aimed to evaluate the viability of seeds of butterfly pea, stylosanthes cv. Campo Grande, tropical kudzu and archer after passage through the gastrointestinal tract (GIT) of goats; and to evaluate these animals as dispersing agents. Fifty grams of seeds of each plant were mixed with the concentrate and given to 20 goats, whose feces were collected up to 102 hours after ingestion for seed retrieval and subsequent germination test. This was a completely randomized design in a factorial arrangement: 4 Fabaceae plants x 17 sampling times with five replicates. The percentage of seed retrieval ranged from 16.9 to 70.9%; butterfly pea and archer, respectively. The passage through the GIT positively affected the germination of kudzu seeds; which presented the highest germination average (45%), and negatively the seeds of stylosanthes and butterfly pea, which presented respectively, 15 and 13%. The period of highest seed dispersal was 24 - 42 hours, peaking in 36 hours. Under these conditions, goats may be considered as legitimate seed dispersers.